Innovation and knowledge spillovers in developing countries - Elif Bascavusoglu (The Open University, Economics Department, 2007)
The purpose of this paper is to evaluate empirically the determinants of innovative activities in emerging countries, with particular attention to national, international and intersectoral knowledge spillovers. Our study concerns 16 emerging and 10 technology source countries, for the period 1980 - 1999 when the majority of the countries studied undertook institutional reforms with the aim of increasing their technological capacity. We introduce foreign knowledge stocks, constructed according to the trade-growth approach, into a knowledge production framework, by means of patent citations. We expand on previous studies by taking into account the role of institutions and various measures of proximity between technology source and recipient countries. Our findings show that emerging countries, although they rely on foreign technology, also benefit from their own R&D efforts. Our results also indicate that the timing of IPR reforms and financing issues are the greatest problems in the innovation process, and highlight the positive role played by international trade in the technology transfer process.
Keywords: F1; F2; O3; 330; innovation; knowledge spillovers; technology transfer; patent citations; Technischer Fortschritt; Technologietransfer; Spillover-Effekt; Schätzung; Entwicklungsländer; Welt